Arenavirus-Mediated Liver Pathology: Acute Lymphocytic Choriomeningitis Virus Infection of Rhesus Macaques Is Characterized by High-Level Interleukin-6 Expression and Hepatocyte Proliferation - Lukashevich, Igor S. (American Society for Microbiology, 2003)
Lymphocytic choriomeningitis virus (LCMV) and Lassa virus can cause hemorrhagic fever and liver disease in primates. The WE strain of LCMV (LCMV-WE) causes a fatal Lassa fever-like disease in rhesus macaques and provides a model for arenavirus pathogenesis in humans. LCMV-WE delivered intravenously or intragastrically to rhesus macaques targets hepatocytes and induces high levels of liver enzymes, interleukin-6 (IL-6), soluble IL-6 receptor (sIL-6R), and soluble tumor necrosis factor receptors (sTNFRI and -II) in plasma during acute infection. Proinflammatory cytokines TNF-α and IL-1β were not detected in plasma of infected animals, but increased plasma gamma interferon was noted in fatally infected animals. Immunohistochemistry of acute liver biopsies revealed that 25 to 40% of nuclei were positive for proliferation antigen Ki-67. The increases in IL-6, sIL-6R, sTNFR, and proliferation antigen that we observe are similar to the profile of incipient liver regeneration after surgical or toxic injury (N. Fausto, Am. J. Physiol. 277:G917-G921, 1999). Although IL-6 was not directly induced by virus infection in vitro, peripheral blood mononuclear cells from acutely infected monkeys produced higher levels of IL-6 upon lipopolysaccharide stimulation than did healthy controls. Our data confirm that acute infection is associated with weak inflammatory responses in tissues and initiates a program of liver regeneration in primates.